OS09.4.A Health-related quality of life in low-grade glioma survivors 26 years after diagnosis. (9th September 2021) - Boele, F W; Reijneveld, J C; de Witt Hamer, P C; van Thuijl, H F; Wesseling, P; Lagerwaard, F J; Taphoorn, M J B; Kouwenhoven, M C M; Snijders, T J; Douw, L; Klein, M
Abstract: BACKGROUND: Many patients with low-grade gliomas (LGGs) continue to survive for many years, yet little is known about patients' health-related quality of life (HRQOL) in long-term survivorship. We previously investigated HRQOL in LGG patients diagnosed on average 6 years prior to assessment (T1, N =195) with a follow-up in stable patients on average 12 years after diagnosis (T2, N =65). We present a final follow-up of LGG survivors (T3), now decades after diagnosis. MATERIAL AND METHODS: We invited patients who participated in our previous assessment ( N =65), regardless of disease status. Patients completed questionnaires to assess HRQOL, fatigue, and depressive symptoms: Short Form-36 Health Survey (SF-36), European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Brain Tumour Module (EORTC BN20), Checklist Individual Strength (CIS), and the Center for Epidemiological Studies Depression Scale (CES-D). Changes over time (T1-T2-T3) on group level and participant level were assessed. RESULTS: Of the 65 patients, 18 (27.7%) were deceased, 3 (4.6%) experienced tumour progression to WHO III, 7 (10.8%) declined, and 3 (4.6%) could not be contacted. Thirty-four patients (52.3%) participated. Of these, 2 had missing HRQOL data, with 32 patients included in analysis. Survivors were M =52.0 (sd=11.3) years old and diagnosed M =26.2 (sd=3.7, range 19–35) years prior. On group level, a statistically significant (but not clinically relevant) improvement in mental health ( p =0.049), and a clinically relevant (but not statistically significant) decline in emotional role functioning was found. No other group-level changes over time in HRQOL were found. Minimal detectable change in HRQOL scale scores over time was observed in individual participants (28.1% only improvement; 25.0% only decline; 21.9% both improvement and decline) with 25.0% remaining completely stable. At T3, 25.0% of survivors scored above the cut-off for high risk of clinical depression (≥16 CES-D), and 53.1% of survivors classed as severely fatigued (≥35 CIS). CONCLUSION: In this cohort of LGG survivors, assessed decades after diagnosis and treatment, HRQOL does not appear to be greatly impacted during survivorship. However, depressive symptoms and fatigue remain relatively common. Findings can help inform patients, their families, and clinicians and can serve as a benchmark for treatment trials evaluating interventions that can have very long-term effects.